Life-cycle inequality: Blacks and whites differentials in life expectancy, savings, income, and consumption - Giacomo De Giorgi; Luca Gambetti; Costanza Naguib (University of Bern, Department of Economics, 2021)
Life expectancy for Blacks is about 8 year shorter than for Whites. A shorter life expectancy, in line with the theoretical prediction of a simple model, determines a much lower amount of savings and wealth accumulation and therefore a lower degree of insurance. This, in turn, contributes to persistent racial differentials in life-cycle consumption.Starting from the same position in the consumption distribution Blacks end up in a lower percentile than Whites after a few decades. This is particularly marked for those Blacks who start at the top of the consumption distribution, where Whites are much more persistent. We document these facts using 40 years of PSID data (1981-2017).
Keywords: E21; E63; D12; C3; 330; Consumption; Income; Earnings persistence; quintile transitions